2016
DOI: 10.1080/15384101.2016.1172147
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of membrane properties of lung cancer cells by azurin enhances the sensitivity to EGFR-targeted therapy and decreased β1 integrin-mediated adhesion

Abstract: In lung cancer, the Epidermal Growth Factor Receptor (EGFR) is one of the main targets for clinical management of this disease. The effectiveness of therapies toward this receptor has already been linked to the expression of integrin receptor subunit β1 in NSCLC A549 cells. In this work we demonstrate that azurin, an anticancer therapeutic protein originated from bacterial cells, controls the levels of integrin β1 and its appropriate membrane localization, impairing the intracellular signaling cascades downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…7 Will azurin be a better and more effective drug in cancer therapy if its lack of toxicity but significant efficacy in clinical trials in cancer patients can be demonstrated? This paper by Bernardes et al 1 in this issue of Cell Cycle is a significant step toward this direction.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…7 Will azurin be a better and more effective drug in cancer therapy if its lack of toxicity but significant efficacy in clinical trials in cancer patients can be demonstrated? This paper by Bernardes et al 1 in this issue of Cell Cycle is a significant step toward this direction.…”
mentioning
confidence: 94%
“…A paper by Nuno Bernardes et al 1 entitled "Modulation of membrane properties of lung cancer cells by azurin enhances the sensitivity to EGFR-targeted therapy and decreased b1 integrin mediated adhesion" in this volume of Cell Cycle aims to gain a better understanding about the mechanism of action of azurin as a therapeutic protein for cancer treatment. Prior to this publication, Dr. Fialho's group reported that azurin targets P-cadherin overexpression in a subset of breast cancer, antagonizing its pro-invasive effects.…”
mentioning
confidence: 99%
“…Azurin is a protein from bacterial origin (Pseudomonas aeruginosa) which in the last years has been studied as an anticancer agent. We and others have identified different modes of action that account for the therapeutic effects of both the entire protein and one lead peptide, p28 [1][2][3][4][5]. The 28 amino acid sequence was first identified as the domain responsible for the penetration of azurin into cancer cells [6] and further studied as an anticancer peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Research with azurin or the derived peptide in the past years have demonstrated that a number of signaling pathways associated with tumor progression and angiogenesis, such as FAK/Src or PI3K/Akt signaling are attenuated after treatment in several cancer models [3,5,13]. Also, functional evidences associated to adhesion to extracellular matrices, invasion and migration of cells are also weakened [5,14], linking the cellular responses to azurin to its possible effects at lipid rafts, which may act as the main gate of azurin to cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation